2021
DOI: 10.1140/epjp/s13360-021-02162-9
|View full text |Cite
|
Sign up to set email alerts
|

A review on the transmission of COVID-19 based on cough/sneeze/breath flows

Abstract: COVID-19 pandemic has recently had a dramatic impact on society. The understanding of the disease transmission is of high importance to limit its spread between humans. The spread of the virus in air strongly depends on the flow dynamics of the human airflows. It is, however, known that predicting the flow dynamics of the human airflows can be challenging due to different particles sizes and the turbulent aspect of the flow regime. It is thus recommended to present a deep analysis of different human airflows b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(26 citation statements)
references
References 107 publications
0
26
0
Order By: Relevance
“…Finally, the aerosol particles released by the Preval sprayer aerosol-based spray system may differ in number and characteristics from those released by people with viral respiratory infections. Previous studies have demonstrated that a cough produces approximately 3,000 droplets, a sneeze releases an estimated 40,000 droplets, and loud speaking may release thousands of droplets per second [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the aerosol particles released by the Preval sprayer aerosol-based spray system may differ in number and characteristics from those released by people with viral respiratory infections. Previous studies have demonstrated that a cough produces approximately 3,000 droplets, a sneeze releases an estimated 40,000 droplets, and loud speaking may release thousands of droplets per second [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Breath droplets or droplets can linger in the air for minutes or hours. [47][48][49][50] Droplets condense enough in tight, poorly ventilated locations to transmit the virus to individuals nearby long after the patient has left the room. [51][52] The potential of Coronavirus spread can be reduced by cleaning and disinfecting frequently touched surfaces, such as tables, doorknobs, furniture, light switches, desks, toilets, taps and sinks.…”
Section: Covid-19 and Surfaces Contaminationmentioning
confidence: 99%
“…The current evidence shows that the respiratory droplets produced by an infected person's sneezing, coughing and spitting are the primary routes of Corona virus transmission among the people [16,38,25]. Healthcare workers might get infected while treating Corona patients.…”
Section: Introductionmentioning
confidence: 99%